2020
DOI: 10.1371/journal.pone.0233197
|View full text |Cite
|
Sign up to set email alerts
|

GCN sensitive protein translation in yeast

Abstract: Levels of protein translation by ribosomes are governed both by features of the translation machinery as well as sequence properties of the mRNAs themselves. We focus here on a striking three-nucleotide periodicity, characterized by overrepresentation of GCN codons and underrepresentation of G at the second position of codons, that is observed in Open Reading Frames (ORFs) of mRNAs. Our examination of mRNA sequences in Saccharomyces cerevisiae revealed that this periodicity is particularly pronounced in the in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…R146 is conserved across eukaryotes, but not prokaryotes [ 12 , 18 ]. Mutational analysis has shown that when R146 is replaced in yeast Rps3, this can lead to lethal or slow growth phenotypes depending on the amino acid substitution, and R146 substitution can affect translation initiation and fidelity [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…R146 is conserved across eukaryotes, but not prokaryotes [ 12 , 18 ]. Mutational analysis has shown that when R146 is replaced in yeast Rps3, this can lead to lethal or slow growth phenotypes depending on the amino acid substitution, and R146 substitution can affect translation initiation and fidelity [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the CAR/mRNA interaction is highly sensitive to the sequence of the +1 codon, with a strong preference of GCN codons [ 12 , 18 ], the sensitivity of different mRNAs to regulation by CAR will depend upon its codon content. The initial codons of ORFs, the “ramp” region, appear to be particularly influential in modulating overall translation levels of mRNAs [ 41 ], perhaps analogous to an entry ramp to a highway determining traffic flow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations